Production, purification, and radiolabeling of the 203Pb/212Pb theranostic pair - Brooke L. McNeil; Andrew K. H. Robertson; Winnie Fu; Hua Yang; Cornelia Hoehr; Caterina F. Ramogida; Paul Schaffer (SpringerOpen, 2021)
Abstract Background Lead-212 (212Pb, t1/2 = 10.6 h) and lead-203 (203Pb, t1/2 = 51.9 h) are an element-equivalent, or a matched theranostic radioisotope pair that show great potential for application in targeted radionuclide therapy (TRT) and single-photon emission computed tomography (SPECT), respectively. At TRIUMF we have produced both 203Pb and 212Pb using TRIUMF's TR13 (13 MeV) and 500 MeV cyclotrons, and subsequently purified and evaluated both radioisotopes using a series of pyridine-modified DOTA analogues in comparison to the commercially available chelates DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) and TCMC (1,4,7,10-tetraaza-1,4,7,10-tetra(2-carbamoylmethyl)cyclododecane). Results Proton irradiation (12.8 MeV) of natural and enriched thallium-203 (203Tl) targets gave 203Pb saturation yields of 134 ± 25 and 483 ± 3 MBq/μA, respectively. Thorium-228 (228Th, t1/2 = 1.9 y), a by-product of 232Th proton spallation on TRIUMF's main 500 MeV beamline (beamline 1A, BL1A), was recovered to build a 228Th/212Pb generator with the ability to deliver up to 9-10 MBq of 212Pb daily. Both lead isotopes were purified via solid phase extraction chromatography (Pb resin), and isolated in an acetate form ([203/212Pb]Pb(OAc)2) suitable for direct radiolabeling of chelators and bioconjugates. A series of cyclen-based chelators (herein referred to as DOTA-1Py, -2Py, and -3Py) along with established chelates DOTA and TCMC were evaluated for their ability to complex both 203Pb and 212Pb. All chelates incorporated 212Pb/203Pb efficiently, with higher radiolabeling yields observed for the 212Pb-complexes. Conclusion The production of 203Pb and 212Pb was established using TRIUMF 13 MeV and 500 MeV cyclotrons, respectively. Both production methods provided radiometals suitable for subsequent radiolabeling reactions using known and novel chelates. Furthermore, the novel chelate DOTA-3Py may be a good candidate for biomolecule conjugation and further theranostic 212Pb/203Pb studies.